Stock Market’s Reaction to Disclosure of Environmental Violations: Evidence from China - Xu, X. D.; Zeng, Saixing; Tam, Chiming (2012)
The stock market’s reaction to information disclosure of environmental violation events (EVEs) is investigated multi-dimensionally for Chinese listed companies, including variables such as pollution types, information disclosure sources, information disclosure levels, modernization levels of the region where the company locates, ultimate ownership of the company, and ownership held by the largest shareholder. Using the method of event study, daily abnormal return (AR) and accumulative abnormal return (CAR) are calculated under different event window for examining the extent to which the stock market responds to the EVEs. Furthermore, statistical significance of the difference in stock market reaction is compared between event firms with different characteristics. The relationship between CAR and its impact factors is examined by multivariate analysis. The findings reveal that the average reduction in market value is estimated to be much lower than the estimated changes in market value for similar events in other countries, demonstrating that the negative environmental events of Chinese listed companies currently have weak impact on the stock market.
Keywords: Event window; Event Study; Stock Market; Information Disclosure; Environmental violation events